Examining clinical outcomes utilizing low-pressure pneumoperitoneum during robotic-assisted radical prostatectomy. Issue 3 (September 2016) - Christensen, Cody; Maatman, Thomas; Maatman, Thomas; Tran, Tony
Abstract The objective of the study was to assess the safety and clinical outcomes of performing RARP utilizing LPP 12 mmHg with locally confined adenocarcinoma of the prostate. Utilizing the Metro Health RALP database registry and the Michigan Urological Clinic records, we retrospectively reviewed the records of consecutive RALPs performed between December 2012 and March 2015 by a single robotic surgeon. 100 patients underwent RARP utilizing 15 mmHg of standard pressure pneumoperitoneum (SPP) and 100 patients underwent RALP utilizing 12 mmHg lower pressure pneumoperitoneum (LPP). Intraoperative parameters reviewed included operative time (OT) and blood loss (BL). Postoperative parameters reviewed included length of hospital stay (LOS), postoperative ileus, fistulas, urinary retention and hematoma formation. Surgical outcomes reviewed included pathological stage and combined Gleason score. Patient age, BMI, mean combined Gleason score and pathological stage were similar in both groups. Mean OT for the LPP group was 105.49 (66–166) and for the standard pressure pneumoperitoneum (SPP) group 111.31 (61–231) min. The length of stay in both groups was similar, averaging 1.53 (1–6) days for the LPP group and 1.57 (1–6) days for the SPP group. The LPP group had a lower postop ileus rate of 4 vs 8 % in the SPP group, but they were not statistically different. Likewise, the positive margin rate, readmission rate, hematoma rate, retention rate and urinary fistula rate were similar and not statistically different for both groups. Pneumoperitoneum of 12 mmHg is noninferior to 15 mmHg during RARP and does not alter the clinical outcomes.